Brain-derived neurotrophic factor Val66Met genotype modulates amygdala habituation. (30th May 2017) - Perez-Rodriguez, M. Mercedes; New, Antonia S.; Goldstein, Kim E.; Rosell, Daniel; Yuan, Qiaoping; Zhou, Zhifeng; Hodgkinson, Colin; Goldman, David; Siever, Larry J.; Hazlett, Erin A.
Abstract: A deficit in amygdala habituation to repeated emotional stimuli may be an endophenotype of disorders characterized by emotion dysregulation, such as borderline personality disorder (BPD). Amygdala reactivity to emotional stimuli is genetically modulated by brain-derived neurotrophic factor (BDNF) variants. Whether amygdala habituation itself is also modulated by BDNF genotypes remains unknown. We used imaging-genetics to examine the effect of BDNF Val66Met genotypes on amygdala habituation to repeated emotional stimuli. We used functional magnetic resonance imaging (fMRI) in 57 subjects (19 BPD patients, 18 patients with schizotypal personality disorder [SPD] and 20 healthy controls [HC]) during a task involving viewing of unpleasant, neutral, and pleasant pictures, each presented twice to measure habituation. Amygdala responses across genotypes (Val66Met SNP Met allele-carriers vs. Non-Met carriers) and diagnoses (HC, BPD, SPD) were examined with ANOVA. The BDNF 66Met allele was significantly associated with a deficit in amygdala habituation, particularly for emotional pictures. The association of the 66Met allele with a deficit in habituation to unpleasant emotional pictures remained significant in the subsample of BPD patients. Using imaging-genetics, we found preliminary evidence that deficient amygdala habituation may be modulated by BDNF genotype. Graphical abstract: Highlights: Amygdala habituation is abnormal in borderline personality disorder. The role of BDNF Val66Met genotypes in habituation is unknown. We used imaging-genetics to test the effect of BDNF genotype on habituation. BDNF Val66Met genotypes modulate amygdala habituation.